2013
DOI: 10.4318/tjg.2013.0571
|View full text |Cite
|
Sign up to set email alerts
|

Expression and significance of IGF-2, PCNA, MMP-7, and ?-actin in gastric carcinoma with Lauren classification

Abstract: Amaç: Kanser hücrelerinde insülin-benzeri büyüme faktörü-2, prolifere edici hücre nükleer antijeni, matriks metalloproteinaz-7'nin ekspresyon ve da¤›l›m›n› ve interstisyel miyofibroblastlarda α-aktin ekspresyonunu tespit ederek insulin-like growth factor-2, proliferating cell nuclear antigen, matrix metalloproteinase-7, and α-actin in the gastric tissue was significantly higher than in the normal gastric mucosa. Insulin-like growth factor-2 was mainly expressed in the nucleus in diffuse gastric cancer and in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…PCNA plays a pivotal role in numerous cellular processes, for instance DNA replication, cell cycle progression, transcription, and chromosome segregation [ 29 , 30 , 31 ]. Consequently, it has been previously reported that the expression level of PCNA was higher in cancer cells and cancer tissues, such as breast, gastric, and lung cancer [ 32 , 33 , 34 , 35 ]. It has been found that novel classes of the compound known as PCNA inhibitor (PCNA-I1) can directly bind to PCNA, stabilize PCNA trimers, decrease PCNA–chromatin association, and inhibit tumor cell growth by inducing a cell cycle arrest [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…PCNA plays a pivotal role in numerous cellular processes, for instance DNA replication, cell cycle progression, transcription, and chromosome segregation [ 29 , 30 , 31 ]. Consequently, it has been previously reported that the expression level of PCNA was higher in cancer cells and cancer tissues, such as breast, gastric, and lung cancer [ 32 , 33 , 34 , 35 ]. It has been found that novel classes of the compound known as PCNA inhibitor (PCNA-I1) can directly bind to PCNA, stabilize PCNA trimers, decrease PCNA–chromatin association, and inhibit tumor cell growth by inducing a cell cycle arrest [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Evidence is accumulating that patient prognosis and treatment response depend not only on the tumor stage but also on tumor-specific alterations of both gene expression and various signaling pathways. The two major histological subtypes of GC according to Laurén, diffuse-type and intestinal-type GC, have distinct tumor dissemination patterns and show diverse pathogeneses and expression profiles, likely resulting from molecular differences in tumor epithelial and stroma cells [ 4 , 5 ]. Although the distinction between diffuse and intestinal subtype in GC has prognostic significance, it is still widely neglected in patient-tailored treatment of GC [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…breast cancer [29], gastric cancer [30], prostate cancer [31], and NSCLC [32]. In our study, MMP9 showed distinctive biological activity levels in different subtypes of lung adenocarcinoma.…”
mentioning
confidence: 49%
“…Expression of genes involved in tumor cell invasion and metastasis were upregulated between 10‐fold (MMP2) and 5000‐fold (MMP9), increased gene expression of MMP9, and decreased gene expression of tumor suppressor p53 was associated with poor tumor differentiation . Moreover, the level of MMP9 expression was also correlated with cancer classification and overall survival of breast cancer , gastric cancer , prostate cancer , and NSCLC . In our study, MMP9 showed distinctive biological activity levels in different subtypes of lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%